New Public Service: Pelayanan Lansia Di Puskesmas Karawaci Baru Kota Tangerang - Najwa Ardelia Rahmawati; Muhammad Ibrahim Rantau; Pri Utami (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2026)
This study aims to analyze the implementation of the New Public Service principle at the Karawaci Baru Community Health Center in Tangerang City, especially in elderly care. Elderly health care is one of the strategic issues in the primary health care system along with the increasing number of elderly population. In providing primary health care, the Community Health Center coordinates with the network and network system in its working area, which includes coaching, health services, reporting recording, logistical supply, and/or referrals. This study uses the theory of Denhardt & Denhardt (2007) which includes: Serve citizens not customers, Seek the public interest, Value citizenship over entrepreneurship, Think strategically act democratically, Recognize that accountability is not simple, Serve rather than steer, Value people not just productivity. The New Public Service Principle has not been implemented at the Karawaci Baru Community Health Center even though the Mobile Assistant Community Health Center (Pustuling) has been established. Based on the results of observations, the main problems were found: 1) Long waiting time for elderly health care, 2) Imbalance between the number of medical personnel and patients, 3) Lack of follow-up of elderly health care. Indicators related to the main problem are: Serve citizens not customers, Value Citizenship Over Entrepreneurship, Think strategically act democratically, and Recognize that accountability is not simple. The research method used is descriptive qualitative with a post-positivism paradigm, through data collection techniques in the form of interviews, observations, and documentation studies. Therefore, it is necessary to strengthen aspects of community participation, service flexibility, balance between administrative accountability and patient needs, and improve the quality of services that are more centered on the elderly so that the implementation of the principles of New Public Service in elderly health services can be realized more optimally and comprehensively.